FORMULASI EMULGEL SARI BUAH TOMAT DAN OCTYL METHOXYCINNAMATE SERTA UJI NILAI SPF - lidia lidia (Jurnal Penelitian Farmasi Indonesia, 2017)
Sunscreen is a preparation containing substances that can absorb and / or reflect back the exposed ultraviolet rays on the skin. The compounds commonly used as sunscreens are octyl methoxycinnamate which chemically absorbs UV light into the epidermal layer of the skin. However, this substance has a deficiency that is photolabil causing reduced efficacy of UV filters from sunscreen (Draelos & Thaman, 2006). Lycopene compounds in tomatoes are antioxidants that have photoprotective nature (Svobodova et al, 2003). Based on some previous research states that the content of lycopene in tomatoes (Solanum lycopersicum L.) can be used to protect the skin from ultraviolet radiation. The aim of this research is to know whether tomato’s extract and octyl methoxycinnamate can be formulated into emulgel and what is SPF value obtained from emulgel preparation of tomato’s extract combination and octyl methoxycinnamate. The emulgel was evaluated, including organoleptic examination, homogeneity, pH, viscosity, dispersion, freeze thaw test, irritation test, and for the most stable formula determined SPF value by measuring absorbance of sample solution at 290-320 nm wavelengths at interval 5 nm using a UV-Vis spectrophotometer. The results showed that the third emulgel formula has the best stability among the three formulas and has an SPF value of 29.32 ± 0.030 under the ultra-protection category.